Progress in the Enzymology of the Mitochondrial Diseases of Lipoic Acid Requiring Enzymes - Cronan, John E. (Frontiers in Genetics, 2020)
Three human mitochondrial diseases that directly affect lipoic acid metabolism result from heterozygous missense and nonsense mutations in the LIAS, LIPT1 and LipT2 genes. However, the functions of the proteins encoded by these genes in lipoic acid metabolism remained uncertain due to a lack of biochemical analysis at the enzyme level. An exception was the LIPT1 protein for which a confusing activity had been reported. This activity led to several models, some contradictory, to accommodate the role of LIPT1 protein activity in explaining the phenotypes of the afflicted neonatal patients. Recent evidence indicates that this LIPT1 protein activity is a misleading evolutionary artifact and that the physiological role of LIPT1is in transfer of lipoic acid moieties from one protein to another. This and other new biochemical data now define a straightforward pathway that that fully explains each of the human disorders specific to the assembly of lipoic acid on its cognate enzyme proteins.